Preeclampsia - Abduljabbar, Hassan (IntechOpen, 2022)
Preeclampsia is a disorder of pregnancy characterized by high blood pressure, edema, and proteinuria that affects 2%-8% of pregnancies worldwide. Hypertensive disorders of pregnancy, including preeclampsia, are among the most common causes of death in pregnant persons. Over six chapters, this book examines the pathophysiology of preeclampsia, vitamin D deficiency as a risk factor for preeclampsia, the cellular changes that occur with preeclampsia, associated organ dysfunction, gestational endotheliopathy, and ophthalmic complications of preeclampsia.